2008
DOI: 10.1093/her/cyn007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an interactive, Internet-based weight loss program: a pilot study

Abstract: The Internet can access a large number of consumers in a more cost-effective manner than other information delivery channels. In this pilot study, we assessed whether an online weight reduction program including dietary advice plus exercise (ED) was more effective in reducing weight than an exercise-only program (EX) >12 weeks. Participants were randomized to either the ED or EX group and attended a center for anthropometric measurements and dietary assessment. Both groups wore a pedometer and set weekly goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(118 citation statements)
references
References 38 publications
2
112
0
4
Order By: Relevance
“…when saturation was achieved. 16 Twentyseven papers were included in the final diversity sample, reporting interventions for: physical activity [17][18][19][20][21][22][23][24][25][26][27][28][29] ; smoking cessation [30][31][32][33][34] ; weight [35][36][37] ; physical activity and nutrition 38 ; nutrition 39 ; chronic pain 40 ; dyspnea 41 ; arthritis 42 ; and breast cancer risk. 43 Four of these programmes contained telemedicine components.…”
Section: Phase 1 Diversity Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…when saturation was achieved. 16 Twentyseven papers were included in the final diversity sample, reporting interventions for: physical activity [17][18][19][20][21][22][23][24][25][26][27][28][29] ; smoking cessation [30][31][32][33][34] ; weight [35][36][37] ; physical activity and nutrition 38 ; nutrition 39 ; chronic pain 40 ; dyspnea 41 ; arthritis 42 ; and breast cancer risk. 43 Four of these programmes contained telemedicine components.…”
Section: Phase 1 Diversity Samplingmentioning
confidence: 99%
“…43 Four of these programmes contained telemedicine components. 30,35,40,41 Review strategy. The design features used to deliver interventions were first identified.…”
Section: Phase 1 Diversity Samplingmentioning
confidence: 99%
“…Participants in 2 positive trials were relatively homogenous (Ͼ80% female and white), 56,60 whereas participants in 2 others were more diverse (eg, Ϸ50% male and 50% white). 55,57 An additional 7 of the 18 trials reported no significant differences in weight loss between the Internet and control conditions, 58,[63][64][65][66][67]71 and the final 2 trials reported significantly greater weight loss among participants randomized to the control condition. The superior control condition was a self-directed weight loss manual in 1 study 68 and face-to-face counseling in another study.…”
Section: Internet-based Studiesmentioning
confidence: 98%
“…Second, positive trials reported completer rather than intention-to-treat analyses. 61,63,71,65 This compromises the value of randomization. Third, attrition rates in some studies were high.…”
Section: Internet-based Studiesmentioning
confidence: 99%
“…The patients would be able to access educational material at their time of convenience and that will improve their understandings of the disease information [6,2]. OPE is unequivocally amongst the most effective methods of patient education [23,24]. Therefore, it is highly likely that OPE will assist carers and professionals in providing health education to patients and healthcare consumers.…”
Section: Benefits Of Online Patient Educationmentioning
confidence: 99%